< Chan Chan > and its etymological trap: response to Cerrón-Palomino - Urban, Matthias (2022)
This contribution concerns once again the name of Chan Chan, the largest pre-Hispanic city in the Americas. Rodolfo Cerrón-Palomino has recently argued that the name should be etymologized through a combination of Quechua, which had a weak and short-lived presence on the Peruvian North Coast, and Aymara material, a language which had no known presence there at all. In addition to this major flaw, I discuss further problematic aspects of the proposal. Each of these would suffice to cast considerable doubt on the proposed etymology, but in conjunction they make it advisable to reject it outright. Instead, I continue to defend a methodologically conservative and cautious posture that I have already advocated in my earlier contribution to the topic